Exploring self-esteem and personality traits as predictors of mental wellbeing among Chinese university students: the mediating and moderating role of resilience - Cui, Zhenti; Lin, Zihan; Ren, Jingjie; Cao, Yingdong; Tian, Xiaofei (Frontiers in Psychology, 2024)
Understanding the factors influencing mental well-being among university students is crucial. This study explores the predictive roles of self-esteem and personality traits while considering the mediating and moderating effects of resilience. A cross-sectional survey was conducted among Chinese university students (N = 689, mean age = 20.3 years) during April to July in 2022. Mental well-being was assessed using the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS). Resilience was measured with the revised Connor-Davidson Resilience Scale (CD-RISC) and personality traits and self-esteem were evaluated using the Chinese version of the Big Five Inventory-2(BFI-2) and Texas Social Behavior Inventory (TSBI) separately. Data were analyzed using four step regression for mediation analysis and moderation analyses. Self-esteem and personality traits exhibited significant correlations with resilience and mental well-being. Resilience partially mediated the relationship between self-esteem and mental well-being and fully mediated some of the relationship between personality traits and mental wellbeing. Furthermore, moderation analyses revealed that tenacity and autonomy moderated the associations between specific personality traits and mental well-being. In conclusion, this study sheds light on the complex interplay of self-esteem, personality traits, resilience, and mental well-being among Chinese university students. Recognizing the importance of resilience in this relationship offers valuable insights for interventions aimed at promoting mental well-being among this population. These findings emphasize the multifaceted nature of mental well-being and call for comprehensive approaches in supporting university students' mental health.